Treating Schizophrenia: Open Conversations and Stronger Relationships Through Psychoeducation and Shared Decision-Making - Mucci, Armida; Kawohl, Wolfram; Maria, Cristiana; Wooller, Annette (Frontiers in Psychiatry, 2020)
Integrated pharmacological and psychosocial treatments, such as psychoeducation (PE) and shared decision-making, have been shown to significantly improve outcomes for people living with schizophrenia (PLWS). Underpinning the success of these interventions is a strong therapeutic relationship between PLWS, their carers and their healthcare team. While many recognize the value of this relationship, implementation of the interventions necessary to facilitate its construction remains low. In this article, we identify the barriers to developing productive therapeutic relationships and explain how PE and shared decision-making can improve adherence to treatment, strengthen therapeutic relationships and ultimately equip patients to achieve better functional outcomes.